Do Rewards Matter for Managing Knowledge through Empowering Knowledge Workers? - Ayesha Nazisha; Muhammad Ilyas; Yasir Aftab Farooqi; Rabia Amjad (UW Journal of Management Sciences, 2022)
Purpose: The purpose of the study revolves around understanding the relationship of intrinsic and extrinsic rewards associated with knowledge management practices, the relationship is further explored with psychological empowerment as mediator between rewards and KM practices. Methodology/Design: The study falls under the category of positivism as deductive approach is most suitable. The data was collected using a structured questionnaire from different colleges of multiple cities of Pakistan. The sample was drawn on basis of cluster sampling technique. Initially 390 questionnaires were distributed among the teachers, out of which 263 completely filled questionnaires were used for data analysis using SPSS (Statistical Package for Social Sciences) and AMOS. Findings and Implications: Results of this study indicated strong positive impact of intrinsic rewards and psychological empowerment with knowledge management practices while no significant linkage of extrinsic rewards was found with knowledge management. Moreover current study has indicated that intrinsic rewards are of greater importance to people than extrinsic rewards. Results suggested that in order to produce knowledge management culture in organizations particularly knowledge oriented ones, it is necessary for the supervisors and managers to devise such environment and policies where individuals are given empowerment and rewards of intrinsic nature so that they are motivated to get involved in knowledge management practices which may provide competitive edge to the organization. Limitations: The study has limited generalization due to small sample size. Another aspect is cross-sectional nature of the study.